The Role of Green Ports in Enhancing Environmental Sustainability: ((An Analytical study of the related Literature)) - Lafta, Hasanain; Abdulabbas, Abbas (The Gulf Economist, 2025)
The study emphasizes the importance of green ports in achieving environmental sustainability, especially in light of the urgent issue of climate change. Although the maritime sector is essential for international trade, it also contributes significantly to local pollution and greenhouse gas emissions. The study followed in its methodology and design to conduct a survey and analysis of the literature related to green ports and environmental sustainability, as the study focused on extracting seven main dimensions (air pollution management, cybersecurity in relation to port security, noise and oil pollution management, water pollution management by hazardous organisms, adaptation to climate change, use of renewable energy, waste management) as important dimensions for implementing green ports Based on green port indicators. A roadmap is formed to achieve improvement and environmental sustainability in port operations. The study reached a number of conclusions, the most important of which is that the process of transforming to green ports is not without challenges. It requires large initial investments, comprehensive planning, and adaptation to new technologies and regulations. Weak participation of government institutions in general and institutions concerned with port operations in particular to take effective and efficient steps towards adopting green practices that contribute to achieving environmental sustainability in port operations which can be applied in the Grand Faw Port. Keywords: Green port, sustainability, green performance, maritime industry, energy power.